2020
DOI: 10.1088/1361-6641/ab75a5
|View full text |Cite
|
Sign up to set email alerts
|

Structural and luminescence imaging and characterisation of semiconductors in the scanning electron microscope

Abstract: The scanning electron microscopy techniques of electron backscatter diffraction (EBSD), electron channelling contrast imaging (ECCI) and cathodoluminescence (CL) hyperspectral imaging provide complementary information on the structural and luminescence properties of materials rapidly and non-destructively, with a spatial resolution of tens of nanometres. EBSD provides crystal orientation, crystal phase and strain analysis, whilst ECCI is used to determine the planar distribution of extended defects over a larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Various studies reported in the literature have shown that ECCI analysis can also provide information on the threading dislocation type present in c-plane GaN. 41,49,50 This does usually involve knowledge of the exact diffraction condition, in order to analyze the change of the contrast in relation to the diffraction vector g. But even without knowing the exact diffraction condition, a differentiation between pure edge and mixed/pure screw-type dislocations can be made by utilizing the change in ECCI contrast on the dislocations. This is due to the fact that the contrast of pure edge dislocations is independent of the diffraction vector g and only depends on their Burgers vector b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies reported in the literature have shown that ECCI analysis can also provide information on the threading dislocation type present in c-plane GaN. 41,49,50 This does usually involve knowledge of the exact diffraction condition, in order to analyze the change of the contrast in relation to the diffraction vector g. But even without knowing the exact diffraction condition, a differentiation between pure edge and mixed/pure screw-type dislocations can be made by utilizing the change in ECCI contrast on the dislocations. This is due to the fact that the contrast of pure edge dislocations is independent of the diffraction vector g and only depends on their Burgers vector b.…”
Section: Resultsmentioning
confidence: 99%
“…36,50 The black-white contrast of edge dislocations originates from the tensile-compressive strain profile across the edge dislocation, and, thus, any change in the diffraction contrast that is different from a 0 or 180 flip indicates that the dislocation has a screw component. 49 This methodology has been tested thoroughly for c-plane GaN but has, to the best of our knowledge, not been studied theoretically or experimentally on semi-polar GaN. The main difference in comparison to c-plane GaN is the inclination angle of the threading dislocations when they intersect the surface.…”
Section: Resultsmentioning
confidence: 99%
“…Scanning electron microscopy (SEM) is another imaging tool that can characterize samples like tissue sections, cells or nanoparticles by attaining information about the morphology, structure and composition. 21 Images are obtained by the detection of a variety of signals such as secondary electrons and backscattered electrons that are frequently used for biological samples' imaging, alongside X-rays and cathodoluminescence. 22 Energy-dispersive spectroscopy (EDS) is used for the semi-quantitative and qualitative analysis of the chemical elements of samples by the analysis of two types of radiations which are continuous radiation that results in the formation of the background of the measurement and the characteristic radiation of a specic wavelength resulting in the detection of the elemental composition.…”
Section: Introductionmentioning
confidence: 99%
“…Structural analysis of nano‐ and micro‐materials is essential in various material sciences such as polymers, 1–4 energy materials, 5,6 semiconducting materials, 7–9 and biomaterials 10–16 . Depending on the size and properties of the material, sophisticated pretreatment, and observation techniques are essentially required.…”
Section: Introductionmentioning
confidence: 99%